Bispectral Methods of Signal Processing : Applications in Radar, Telecommunications and Digital Image Restoration - Totsky, Alexander V., 1952-; Zelensky, Alexander A., 1943-; Kravchenko, Viktor F., 1939- (Walter de Gruyter GmbH, 2015)
By studying applications in radar, telecommunications and digital image restoration, this monograph discusses signal processing techniques based on bispectral methods. Improved robustness against different forms of noise as well as preservation of phase information render this method a valuable alternative to common power-spectrum analysis used in radar object recognition, digital wireless communications, and jitter removal in images.